COLOMINA-ALMIÑANA, Juan José (2018): Formal Approach to the Metaphysics of Perspectives. Points of View as Access. Heidelberg: Springer. - David Pérez Chico (Daimon)
Se trata de una reseña del libro de Juan José Colomina-Almiñana, Formal Approach to the Metaphysics of Perspectives. Points of View as Access, Heidelberg, Springer International Publishing (Synthese Library, volume 392), 2018.